Comparison between aspiration and incision and drainage of breast abscess (Journal of Surgical Sciences, 2020)
Background: Breast abscess is defined as an acute inflammatory lump which yields pus on incision/aspiration. The frequency of occurrence is highly related to pregnancy and caused due to nipple cracking by a child during breast feeding and bacterial colonization due to improper nursing technique and incomplete emptying of the breast. Objective: The present study compares the outcome and effectiveness of traditional treatment incision and drainage against needle aspiration in the treatment of breast abscess.Methods: This is a comparative study carried out in department of general surgery, SherE- Bangla Medical College Hospital, Barisal between January 2014 and December 2014. 50 female patients of age between 20-40 years and diagnosed breast abscess with abscess size of 5'7 cm in diameter on ultrasonography were included in the study after taking written consent form. Of these 25 had undergone aspiration of the breast abscess (group A) and 25 had undergone incision and drainage (group B).Results: The mean age of the female patients in group A was 23.42 years and in Group B was 23.31. 91% of the cases were lactating. S. aureus was the common organism isolated in both lactating and non-lactating cases, encountered in 27 patients (54%). Out of that were in the aspirated group 17patients (56.67%). 10 patients were in the incised group (33.33%). The mean healing time and cosmetic outcome was significantly (p =0.001) very good in patients treated with needle aspiration compared to incision and drainage. There was no recurrence of breast abscess observed in needle aspiration group during the study. There was 3.3% recurrence rate observed in the incision and drainage group.Conclusion: Breast abscess in patients with diameter of 5'7 cm can be treated with needle aspiration successfully and with a good cosmetic outcome.Journal of Surgical Sciences (2018) Vol. 22 (1): 11-15